2013
DOI: 10.1063/1.4851755
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic strain relaxation and the resulting degree of polarization by one- and two-step growth in nonpolar a-plane GaN grown on r-sapphire substrate

Abstract: Anisotropic strain relaxation and the resulting degree of polarization of the electronic transition in nonpolar a-plane GaN using one-and two-step growth are studied. By using two-step growth, a slower coalescence and a longer roughening-recovery process lead to larger anisotropic strain relaxation, a less striated surface, and lower densities of basal stacking fault (BSF) and prismatic stacking fault (PSF). It is suggested that anisotropic in-plane strains, surface striation, and BSF and PSF densities in nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…16 The degree of polarization of PL in a-plane ZnO should be maintained even when passed through the textured surface layer. Similar to nonpolar a-plane GaN in our previous study, 11 it is suggested that anisotropic in-plane strains, sample quality, and degree of polarization of PL in nonpolar a-ZnO are consequences of the degree of anisotropic strain relaxation. By using the kÁp perturbation approach to simulate the electronic band of nonpolar a-plane ZnO, the transition energy, oscillator strength, and degree of polarization from the conduction band to the highest ðE 1 Þ, second highest ðE 2 Þ, and third highest ðE 3 Þ valence bands are calculated in terms of anisotropic in-plane strains e yy and e zz .…”
Section: A)supporting
confidence: 81%
See 3 more Smart Citations
“…16 The degree of polarization of PL in a-plane ZnO should be maintained even when passed through the textured surface layer. Similar to nonpolar a-plane GaN in our previous study, 11 it is suggested that anisotropic in-plane strains, sample quality, and degree of polarization of PL in nonpolar a-ZnO are consequences of the degree of anisotropic strain relaxation. By using the kÁp perturbation approach to simulate the electronic band of nonpolar a-plane ZnO, the transition energy, oscillator strength, and degree of polarization from the conduction band to the highest ðE 1 Þ, second highest ðE 2 Þ, and third highest ðE 3 Þ valence bands are calculated in terms of anisotropic in-plane strains e yy and e zz .…”
Section: A)supporting
confidence: 81%
“…By using the kÁp perturbation approach to simulate the electronic band of nonpolar a-plane ZnO, the transition energy, oscillator strength, and degree of polarization from the conduction band to the highest ðE 1 Þ, second highest ðE 2 Þ, and third highest ðE 3 Þ valence bands are calculated in terms of anisotropic in-plane strains e yy and e zz . 11,17 The material parameters of ZnO, such as energy parameters, valence band deformation potentials, and elastic stiffness constants, are adopted from Refs. 18 and 19.…”
Section: A)mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] The carrier localization effect caused by indium aggregation and the quantum-confined Stark effect (QCSE) resulting from a strain-induced piezoelectric field in those devices, generally grown along the Ga-polar c-axis [0001], were shown to determine the optical properties and device characteristics. [1][2][3][4][5][6] In spite of successful applications in optoelectronic devices, Ga-polar III-nitrides show some limitations. Because the optimal growth temperatures for the growth of GaN and InN are different, the low-quality, high-In InGaN exhibits a higher defect density and lower green light efficiency, i.e., the well-known "green gap."…”
Section: Introductionmentioning
confidence: 99%